Pengaruh media pembelajaran digital terhadap hasil belajar matematika: meta analisis - Azkia, Nada Fatiyyah; Muin, Abdul; Dimyati, Ahmad (IKIP Siliwangi, 2023)
Therefore, this study aims to determine the influence of digital-based learning media on mathematics learning outcomes, which is examined based on the aspects of educational levels, digital-medias used, and learning materials. The research method is a systematic literature review with meta-analysis. The instrument used is form of article coding sheet containing data for meta-analysis in the form is sample size, mean, and standard deviation of control groups and experiments from articles that have been selected based on the results in the Publish or Perish application and effect size calculations assisted by the OpenMEE application. The result of this study indicates that digital-based learning media has positive influence of 1.115 on mathematics learning outcomes from the 21 articles that were meta-analyzed. Firstly, in terms of education level, digital-based learning media is more effectively used at the elementary level by 1.415. Secondly, in terms of the media used, digital-based learning media is more effective using Macromedia Flash of 1.028. Lastly, in terms of the learning material, digital-based learning media is more effective in Dimensi Tiga by 1.812.